THE EFFECTS OF DISTRIBUTIVE JUSTICE, PROCEDURAL JUSTICE AND INTERACTIONAL JUSTICE ON ORGANIZATIONAL COMMITMENT (Study on Serambi Indonesia Employees of PT.Aceh Media Graphic) - Anis Ilyana; Khairawati; Marbawi; Nurmala (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study to determine the effect of distributive justice, procedural justice, and interactional justice on the organizational commitment of employees at Serambi Indonesia PT Aceh Media Graphic. This study involved 68 permanent employees at Serambi Indonesia. The data collection in this study was carried out using primary data with interviews and questionnaires. The data analysis technique in this study used multiple linear regression analysis and the results showed that Distributive Justice had a positive and significant effect on organizational commitment, procedural justice had a positive and significant effect on organizational commitment and interactional justice had a positive and insignificant effect on organizational commitment. For further research,.